Pengaruh Good Corporate Governance dan Leverage Terhadap Kinerja Keuangan Perusahaan - Perusahaan di Jakarta Islamic Index Periode 2016-2020 - Hesi Eka Puteri; Vira Husna (Faculty of Economics and Business Mulawarman University, 2023)
This study aims to estimate the effect of Good Corporate Governance and Leverage proxied by the board of directors, institutional ownership, audit committee and DAR on financial performance proxied by ROE. The population in this study were companies registered on the Jakarta Islamic Index for the 2016-2020 period, and the sample was taken using a purposive sampling technique, so that a total of 14 companies were determined. The data analysis technique used is the panel data regression method which is a combination of cross section and time series data using E-Views 12. Meanwhile, hypothesis testing uses the GLS model with a probability level of 5%. The findings show that partially the institutional ownership variable has a significant effect on the company's financial performance, while other variables have no significant effect on the financial performance of companies listed on the Jakarta Islamic Index for the 2016-2020 period. Good Corporate Governance and Leverage simultaneously affect the financial performance of companies listed on the Jakarta Islamic Index for the 2016-2020 period.